2002
DOI: 10.1113/jphysiol.2002.023440
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of adenosine, prostaglandins and nitric oxide in hypoxia‐induced vasodilatation: in vivo and in vitro studies

Abstract: Adenosine, prostaglandins (PG) and nitric oxide (NO) have all been implicated in hypoxia-evoked vasodilatation. We investigated whether their actions are interdependent. In anaesthetised rats, the PG synthesis inhibitors diclofenac or indomethacin reduced muscle vasodilatation evoked by systemic hypoxia or adenosine, but not that evoked by iloprost, a stable analogue of prostacyclin (PGI 2 ), or by an NO donor. After diclofenac, the A 1 receptor agonist CCPA evoked no vasodilatation: we previously showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
163
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(180 citation statements)
references
References 45 publications
(112 reference statements)
14
163
1
2
Order By: Relevance
“…Consistent with this observation, an in vitro study clearly demonstrated that prostaglandin inhibition reduced NO formation in response to adenosine stimulation. 14 This observation, which suggests that prostaglandins promote NO synthesis, is also supported by the greater reduction in vascular conductance with inhibition of prostaglandins compared with inhibition of NOS. Therefore, the present findings suggest that the vasodilator response to adenosine, to a large extent, is mediated by prostaglandins and NO and that part of the increased NO formation could be prostaglandin mediated ( Figure 5).…”
Section: Adenosine Vasodilator Response Is Mainly Prostaglandin and Nmentioning
confidence: 54%
See 1 more Smart Citation
“…Consistent with this observation, an in vitro study clearly demonstrated that prostaglandin inhibition reduced NO formation in response to adenosine stimulation. 14 This observation, which suggests that prostaglandins promote NO synthesis, is also supported by the greater reduction in vascular conductance with inhibition of prostaglandins compared with inhibition of NOS. Therefore, the present findings suggest that the vasodilator response to adenosine, to a large extent, is mediated by prostaglandins and NO and that part of the increased NO formation could be prostaglandin mediated ( Figure 5).…”
Section: Adenosine Vasodilator Response Is Mainly Prostaglandin and Nmentioning
confidence: 54%
“…10 -13 Furthermore, in vitro data have suggested that prostaglandins could be involved as a second messenger of adenosine by stimulating NO production. 14 Single inhibition of NO 15,16 or prostaglandin [17][18][19] formation has little or no effect on exercising limb blood flow, but simultaneous inhibition of NO and prostaglandin formation lowers blood flow to exercising limbs by Ϸ30%, 19,20 suggesting that there is an interaction between the prostaglandin and NO systems. It remains unknown whether adenosine contributes to blood flow regulation via direct stimulation of smooth muscle cell P1 receptors and/or by stimulation of endothelial second messengers systems, eg, prostaglandins and NO.…”
mentioning
confidence: 99%
“…However, available evidence in humans suggests that PGs contribute to the rise in skeletal muscle blood flow following periods of limb ischemia (2,10,14,20). Moreover, COX inhibition has been shown to attenuate muscle vasodilation evoked by systemic hypoxia in rats (25). Therefore, it is plausible that the role of PGs in the regulation of muscle blood flow during exercise under conditions of reduced oxygen availability may be enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are based on little to no change in muscle blood flow following PG synthesis inhibition. However, PGs have been reported to be involved in the regulation of skeletal muscle blood flow following periods of ischemia (2,10,14,20) and during systemic hypoxia (25). Therefore, it is possible that the PGs may become a more important vasodilator signal during exercise under conditions of reduced oxygen availability.…”
mentioning
confidence: 99%
See 1 more Smart Citation